Hermeneutika Al-Qur’an Suroh Al-Isro’ Ayat 1 Sebuah Tinjauan Kosmologi - Hasanuddin Chaer; Abdul Rasyad (PALAPA, 2019)
Where is the Islamic view of the hermeneutics of the Qur'an? This article describes the eternal philosophy, I assert that the study of the Qur’an with a hermeneutical approach is very necessary in this era of globalization. This article uses the method of psychological interpretation. The Psychological approach uses cooperative and hunches in understanding the author's soul. This is not only to understand the author from a psychological point of view, but also to get the author's intent from within the text. This article is here to understand and analyze the understanding of the meaning of the esoteric verses of the Qur'an. Contemplation and debate are evidence of the loss of esoteric spiritual-religious understanding of the Qur'an, this understanding recognizes the Qur'an as a sacred / divine reflection that has moral strength, and becomes a moral-spiritual teacher of man. This essay focuses on the idea that the Qur'anic hermeneutics serves to explore the esoteric meaning of the Qur'an as a source of ethics involving the environment and knowledge which can be a valuable resource for the education of the hermeneutical generation.